EFFECT OF SOAKING ON FORMALIN CONCENTRATION - Erdi Nur; Awalia Gusti; Lindawati Lindawati; Rahmi Hidayanti (Universitas Fort De Kock, 2022)
Formalin has banned its use as a food additive as stated in the Minister of Health of RI No.033 in 2012, but is still found to foodstuffs containing formalin. To reduce the impact of formalin, deformalinisasi needs to be done, such as immersion in hot water, or in water leri, and soaking and washing ,. This study aims to determine the difference of soaking and washing the concentration of formaldehyde in various foodstuffs. This study is a quasi-experimental, pretest-posttest design The object of research is to Tahu Tabing, salted Sepat fish, and tuna. This research was conducted with four treatment (15, 30, 45, and 60 minutes) for six times repetition. Data was analyzed using ANOVA. The results showed the largest decline formalin after soaking and washing for 60 minutes, decreased levels of formaldehyde in the Tahu of 31.22%, salted Sepat fish by 6.91%, and the tuna amounted to 2.70%. In statistics show there is a difference of soaking and washing the formaldehyde levels in foodstuffs.